Uma dicotomia para fluxos via fluxos seccional Axioma A - Eduardo, Marcos Fabiano Firbida (2014)
In this work we consider C1 − generic vector fields over a compact, boundaryless, compact, of finite dimension Riemann manifold. The idea is to investigate differential local properties of these vector fields in order to obtain global properties for the induced flow. More precisely, we show if a C1−generic vector field is such that the only singularities accumulated by periodic orbits are co-dimension one singularities then: Either the vector field has a point been accumulated by periodic orbits of different Morse index or the vector field is sectional-Axiom A. Moreover, we show that the existence of points been accumulated by periodic orbits of different indices does not happen for star vector fields having spectral decomposition, which implies these ones should be sectional-Axiom A.